The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.1136/ebmed-2014-110019
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency ablation of Barrett's oesophagus with confirmed low-grade dysplasia reduces risk of development of high-grade dysplasia and adenocarcinoma

Abstract: Commentary on: Phoa KN, van Vilsteren FG, Weusten BL, et al. Radiofrequency ablation vs endoscopic surveillance for patients with Barrett esophagus and low-grade dysplasia: a randomised clinical trial. JAMA 2014;311:1209-17. ContextThe clinical management of patients with suspected low-grade dysplasia in Barrett's oesophagus traditionally involves confirming the diagnosis by repeated systematic biopsy on strong acid suppression therapy and expert histopathological review of the sampled mucosa. Thereafter, pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Radiofrequency ablation of BE with confirmed LGD can reduce risk of developing HGD and adenocarcinoma. 31 The treatment of early or locally advanced EAC may differ greatly and influence the medical cost largely. 32 Therefore, more participants in AS group can lead to detecting more early diseases and reduce postdiagnosis medical cost.…”
Section: Discussionmentioning
confidence: 99%
“…Radiofrequency ablation of BE with confirmed LGD can reduce risk of developing HGD and adenocarcinoma. 31 The treatment of early or locally advanced EAC may differ greatly and influence the medical cost largely. 32 Therefore, more participants in AS group can lead to detecting more early diseases and reduce postdiagnosis medical cost.…”
Section: Discussionmentioning
confidence: 99%
“…16 Similarly, a few other recently published studies have shown that RFA is effective in eradicating dysplasia. 17,18 The above data proved beyond a doubt that RFA has a significant role in treating BE and dysplasia.…”
Section: Discussionmentioning
confidence: 77%
“…Owing to the significant superiority of RFA compared to endoscopic surveillance alone in decreasing progression of LGD to either HGD or esophageal cancer and concern for patient safety if the trial continued, the study was terminated earlier than expected 16 . Similarly, a few other recently published studies have shown that RFA is effective in eradicating dysplasia 17 , 18 . The above data proved beyond a doubt that RFA has a significant role in treating BE and dysplasia.…”
Section: Discussionmentioning
confidence: 99%